Evaluation of a model for providing cost effective, accessible continuing education to the forensic science community - Thomas J. Gluodenis (Taylor & Francis Group, 2021)
This study presents a detailed model and its subsequent assessment for the development and optimized delivery of continuing education for the forensic science community. Online continuing education is on the rise as this modality of content dissemination allows for accessibility, convenience, and affordability. The model, which includes an educational needs assessment, gap analysis, online content delivery and archival, was evaluated through the launch of a global training event/symposium series. The four-year study of over 6 000 participants representing >75 countries provides empirical support for the model based upon registration/attendance data and participant self-assessment surveys. Best practices are identified relative to content and format, operational excellence, technology, and financing of the event. Future directions along with opportunities to further enhance the model are also discussed.Key Points A model is presented for the development, online delivery, and archival of compelling, cost effective continuing education content for the forensic science community. The model is evaluated based upon registration/attendance data and participant surveys. Best practices relative to content and format, operational issues, selection of technology and financing of the event are shared.